e-Publishing: Need of the Hour - B Premlet & Abdul Azeez T A (DESIDOC Bulletin of Information Technology , Vol. 24, No. 2, March 2004, pp. 3-7, 2004)
Electronic journals and electronic books play a crucial role in the changing scenario of libraries and information centres. This paper deals with the emerging technology of electronic publishing. The paper covers e-journals, e-books, advantages of e-journals and e-books, publishers of scholarly e-journals and important e-publishing initiatives